2017
DOI: 10.1002/stem.2631
|View full text |Cite
|
Sign up to set email alerts
|

Tip110 Deletion Impaired Embryonic and Stem Cell Development Involving Downregulation of Stem Cell Factors Nanog, Oct4, and Sox2

Abstract: HIV-1 Tat-interacting protein of 110 kDa, Tip110, plays important roles in multiple biological processes. In this study, we aimed to characterize the function of Tip110 in embryonic development. Transgenic mice lacking expression of a functional Tip110 gene (Tip110 -/-) died postimplantation, and Tip110 -/-embryos exhibited developmental arrest between 8.5 and 9.5 days post coitum. However, in vitro cultures of Tip110 -/-embryos showed that Tip110 loss did not impair embryo growth from the zygote to the blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, this transient and moderate Wt1 overexpression reduced phenotypical cardiomyocyte differentiation, i.e., the percentage of beating clones throughout the observation period. At the onset of differentiation, signaling pathways regulating pluripotency of mESCs are inhibited through downregulation of stem cell genes, such as Sox2, Oct4, and Nanog [ 89 ]. This corresponds to our findings with significant downregulation of these genes at day 3 of differentiation when the first clones started beating.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this transient and moderate Wt1 overexpression reduced phenotypical cardiomyocyte differentiation, i.e., the percentage of beating clones throughout the observation period. At the onset of differentiation, signaling pathways regulating pluripotency of mESCs are inhibited through downregulation of stem cell genes, such as Sox2, Oct4, and Nanog [ 89 ]. This corresponds to our findings with significant downregulation of these genes at day 3 of differentiation when the first clones started beating.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intramolecular and intermolecular disulfide bond formation between any two cysteine residues of HEXIM1 could also contribute to HEXIM1 dimerization and oligomerization. In separate transcriptomics studies, we have shown that Tip110 knockdown and knockout negatively regulated the glutathione metabolic pathway [ 45 , 46 ]. Both mRNA of glutathione reductase (GSR) and glutathione synthetase (GSS), two major enzymes in the glutathione metabolic pathway were found to be 4 times and 2 times lower, respectively in Tip110 knockout embryonic stem cells than those in the Wt counterparts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the onset of differentiation, the signaling pathway regulating pluripotency of hESCs and mESCs is inhibited with the repression of pluripotency genes such as Nanog , Sox2 , and Oct4. 43 Both the Wnt and TGF-β signaling pathways have also been extensively studied for their roles in controlling fate commitment when ESCs start to differentiate into MES. 44 , 45 Similarly, the pathways of DEGs involved in transition from CP to CM are both associated with heart function and related diseases.…”
Section: Discussionmentioning
confidence: 99%